Períodos de estresse térmico durante o crescimento afetam negativamente o desempenho e o rendimento de carcaça de frango de corte - Mello, J. L.M. [UNESP]; Boiago, M. M.; Giampietro-Ganeco, A. [UNESP]; Berton, M. P. [UNESP]; Vieira, L. D.C. [UNESP]; Souza, R. A. [UNESP]; Ferrari, F. B. [UNESP]; Borba, H. [UNESP] (My University, 2015)
The aim of this study was to evaluate the possible effect of exposure of broilers for up to 72 hours of acute heat stress, in different phases of growing, on the performance and carcass yield. Five hundred Cobb male broilers were reared in two climatic chambers equipped with heating and cooling systems. Two hundred and fifty birds were submitted to heat stress (32°C ± 0.5°C), for up to 72 hours, starting at 21 and 35 day old. The remaining 250 birds were kept in thermal comfort throughout the experiment. The environmental heat influenced negatively the body weight (1.595 kg) and feed conversion (1.81) of broilers submitted to heat stress from 21-days-old. After two periods of heat stress, broilers showed lower (p<0.05) feed intake (3.914 kg) and, consequently, body weight (1.958 kg) when compared to control group (4.182 kg and 2.097 kg, respectively). Birds subjected to heat stress at 21 day old showed decrease (p<0.05) of breast yield. The slaughter body weight for broilers from heat stress group decreased after the first and the second expositions to heat. Broilers submitted to periods of acute heat stress after 35 days old shows poor than broilers reared in thermal comfort. There is no influence of heat stress on the commercial cuts yield.
Periods of heat stress during the growing affects negatively the performance and carcass yield of broilers
Keywords: Environment; Feed conversion; Thermoregulation